DESIGN OF ACCOUNTING RECORDING SYSTEM AND FINANCIAL STATEMENTS IN JUNIA SEMPOA SIP - Edvan Josley; Edi Edi (ConCEPt - Conference on Community Engagement Project, 2022)
Accounting and financial reporting systems are very important for business owners in the decision-making process for business development but Junia Sempoa SIP has been established for more than 5 years without an accounting bookkeeping system and still uses manual recording based on tuition invoice and receipts. The purpose of the implementation of this project is to facilitate Junia Sempoa SIP business owner in the process of bookkeeping transactions and the financial position they have. The data collection techniques starts from the process of interviewing, observation and documentation with business owners in the period from September to December 2021. Systems designed using Microsoft Access are capable of generating student lists, cash disbursement forms, cash receipt forms and financial statements. The results of the implementation are expected to help Junia Sempoa SIP business owner in the process of making the right decision in business development and know the financial position owned.